1984
DOI: 10.1093/oxfordjournals.jbchem.a134616
|View full text |Cite
|
Sign up to set email alerts
|

ATP Inactivates Hydrolysis of the K+-Sensitive Phosphoenzyme of Kidney Na+, K+-Transport ATPase and Activates that of Muscle Sarcoplasmic Reticulum Ca2+-Transport ATPase1

Abstract: In order to characterize low affinity ATP-binding sites of renal (Na+,K+) ATPase and sarcoplasmic reticulum (Ca2+)ATPase, the effects of ATP on the splitting of the K+-sensitive phosphoenzymes were compared. ATP inactivated the dephosphorylation in the case of (Na+,K+)ATPase at relatively high concentrations, while activating it in the case of (Ca2+)ATPase. When various nucleotides were tested in place of ATP, inactivators of (Na+,K+)ATPase were found to be activators in (Ca2+)ATPase, with a few exceptions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…K+ did not affect this effect of ATP. Similarly, Fukushima et al (16) observed the same effect of ATP on phosphoenzyme formed by enzyme + ATP. Furthermore, Norby et al (17), in an analysis of transient kinetic experiments on the dephosphorylation in the presence of K+ of phosphoenzyme formed under Na-ATPase conditions, found that K+ decreased the rate of disappearance of EIP (the first in a sequence of three kinetically isomeric phosphoenzyme forms found in Na-ATPase).…”
Section: Kinetic Properties Of Nak-atpasementioning
confidence: 67%
See 1 more Smart Citation
“…K+ did not affect this effect of ATP. Similarly, Fukushima et al (16) observed the same effect of ATP on phosphoenzyme formed by enzyme + ATP. Furthermore, Norby et al (17), in an analysis of transient kinetic experiments on the dephosphorylation in the presence of K+ of phosphoenzyme formed under Na-ATPase conditions, found that K+ decreased the rate of disappearance of EIP (the first in a sequence of three kinetically isomeric phosphoenzyme forms found in Na-ATPase).…”
Section: Kinetic Properties Of Nak-atpasementioning
confidence: 67%
“…During the last ten years a number of techniques have been used to investigate whether Na,K-ATPase is, or is not, a functional dimer.' These include the demonstration of apparent "half-of-the-sites" reactivity in phosphorylation experiments (26), when Ca is substituted for Mg, and in cross-linking experiments (27), as well as ligand-induced cooperactivity under equilibrium conditions (12,13,15,16). This evidence has been reviewed by Glynn (6) and by Askari and Huang (28).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which K þ ions abolish the inhibitory effect of ATP on dephosphorylation cannot be concluded from these studies. However, a feasible hypothesis has been put forward by Fukushima et al (11), who proposed that K þ binding to the phosphoenzyme causes the dissociation of ATP so that it can no longer inhibit dephosphorylation. A critical analysis of this hypothesis would require binding studies to be performed on the phosphoenzyme under conditions where turnover is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…This must involve ATP binding to the phosphorylated form of the enzyme (7)(8)(9)(10). It has also been found that the dephosphorylation reaction of the Ca 2þ -ATPase is accelerated by ATP, which also necessitates ATP binding to the phosphorylated enzyme (10,11). Thus, these results indicate that phosphorylation and ATP binding without phosphorylation are not mutually exclusive reactions for P-type ATPases; i.e., the enzymes can exist in a state in which they are simultaneously phosphorylated and have bound ATP.…”
mentioning
confidence: 99%
“…1) Eisner & Richards, 1983). The alternative pathway may also provide a functional role for enzyme species which bind both phosphate and ATP whose presence has been inferred from binding studies using purified enzyme (Askari & Huang, 1984;Fukushima, Yamada & Nakao, 1984), although the exact relation is unclear since ATP binding to the phosphorylated enzyme retards dephosphorylation without appreciably changing the apparent dissociation constant for phosphate under the conditions of the binding studies. It is worth pointing out that we have proposed (Sachs, 1987) the existence of alternative pathways after E2P2K based on the characteristics of vanadate inhibition of the pump.…”
Section: E2k E1atpmentioning
confidence: 99%